Vplivi okoljskih dejavnikov na prostorsko razporeditev evropske srne (srnjadi) (Capreolus capreolus L.) v Gorenjskem lovskoupravljavskem območju - Hafner, Miran (Gozdarski vestnik, 2017)
In our research we studied which factors affect spatial distribution of roe deer (Capreolus capreolus L.) in Gorenjsko hunting management district. The research is based on the sample of N = 2.196 georeferenced harvest locations of N = 42.468 animals and GIS-data layers of 21 environmental variables. Logistic regression predicts, that the adequacy of the space for roe deer habitat is conditioned by the values of thirteen environmental variables: variables of space structure (share of agricultural land, share of inaccessible areas, length of public roads, length of forest margin, exposition), climatic variables (amount of precipitation, amount of sun exposure in the summer, mean annual temperature), variables of forest stands structure (share of stands in regeneration, share of young forest, growing stock of stands, indicator of forest associations, length of forest roads). With another model we also discovered a negative impact by the distance to the first forest and agricultural area. Among the agricultural areas, the adequacy of the space for roe deer habitat is most affected by the share of meadows and share of fields and gardens.
Keywords: evropska srna; Capreolus capreolus; habitat; roe deer; Gorenjsko hunting management; Gorenjsko lovskoupravljalsko območje; Slovenia; Slovenija